Spontaneous pneumoperitoneum by ruptured pyogenic liver abscess - Neirotti, Rubens (Cirugía del Uruguay, 1998)
The authors present two exceptional cases of pneumoperitoneum secondary to the rupture of gas-producing hepatic pyogenic abscesses. Both were diagnosed as acute abdomen cases due to hollow viscus perforation based on radiological evidence of air at subphrenic leve/ (pneumoperitoneum). In two cases urgent laparotomy showed, contrary to what was expected, hollow viscus indemnity and rupture of hepatic pyogenic abscess associated to diffuse peritonitis. According to our knowledge, pneumoperitoneum secondary to the rupture of gas-producing hepatic pyogenic abscess is extreme/y rare